Neurotrophin Receptor p75NTR Regulates Immune Function of Plasmacytoid Dendritic Cells - Bandoła, Joanna; Richter, Cornelia; Ryser, Martin; Jamal, Arshad; Ashton, Michelle P.; von Bonin, Malte; Kuhn, Matthias; Dorschner, Benjamin; Alexopoulou, Dimitra; Navratiel, Katrin; Roeder, Ingo; Dahl, Andreas; et al. (Frontiers in Immunology, 2017)
Plasmacytoid dendritic cells (pDCs) regulate innate and adaptive immunity. Neurotrophins and their receptors control the function of neuronal tissue. In addition, they have been demonstrated to be part of the immune response but little is known about the effector immune cells involved. We report, for the first time, the expression and immune-regulatory function of the low affinity neurotrophin receptor p75NTR by the antigen-presenting plasmacytoid dendritic cells (pDCs), mediated by Toll-like receptor (TLR) 9 activation and differential phosphorylation of interferon regulatory factor (IRF) 3 and 7. The modulation of p75NTR on pDCs significantly influences disease progression of asthma in an ovalbumin-induced mouse model mediated by the TLR9 signaling pathway. p75NTR activation of pDCs from patients with asthma increased allergen-specific T cell proliferation and cytokine secretion in NGF concentration dependent manner. Further, p75NTR activation of pDCs delayed the onset of autoimmune diabetes in RIP-CD80GP mice and aggravated Graft-versus-Host disease in a xenotransplantation model. Thus, p75NTR signaling on pDCs constitutes a new and critical mechanism connecting neurotrophin signaling and immune response regulation with great therapeutic potential for a variety of immune disorders.